Verifikasi Keabsahan Fotokopi Bukti Surat Bertandatangan Elektronik QR Code pada Sidang Daring dan Sidang Tatap Muka - Pakpahan, Novritsar Hasintongan (Ikatan Hakim Indonesia (IKAHI), 2023)
The development of judicial information technology is increasingly felt its function when the world is experiencing a global COVID-19 pandemic in 2020. The pandemic requires a health protocol, namely the limitation of distance and contact between individuals in order to prevent the chain of spread of the COVID-19 outbreak. As a result, trials that are usually conducted face-to-face must be limited in order to prevent the spread of the COVID-19 outbreak. Problems arise when a lot of evidence in legal practice involves the use of letter evidence with electronic QR Code signatures that have not been regulated in procedural law, especially in terms of submitting photocopies as proof of letters such as family cards and marriage certificates. This research aims to find out and describe the techniques for judges in verifying the validity of copies or photocopies of letters with electronic QR Code signatures submitted as letter evidence in court both online and face-to-face. This type of research is normative legal research using descriptive analysis method. The results showed that the implementation of checking the validity of letter evidence must still be carried out in accordance with the provisions of criminal procedural law and civil procedural law using an android-based mobile phone through the VeryDS application issued by the Indonesian Electronic Certification Centre or through sending QR Code electronic signature samples via the web